Recent Advances and Future Directions of Hypothermia Therapy for Traumatic Brain Injury - SUEHIRO, Eiichi (Neurol Med Chir (Tokyo), 2014)
For severe traumatic brain injury (TBI) patients, no effective treatment method replacing hypothermia therapy has emerged, and hypothermia therapy still plays the major role. To increase its efficacy, first, early introduction is important. Since there are diverse pathologies of severe TBI, it is necessary to appropriately control the temperature in the hypothermia maintenance and rewarming phases by monitoring relative to the pathology. Currently, hypothermia is considered appropriate for severe TBI patients requiring craniotomy for removal of hematoma, while induced normothermia is appropriate for severe TBI patients with diffuse brain injury. Induced normothermia is expected to exhibit a cerebroprotective effect equivalent to hypothermia, as well as reduce the complexity of whole-body management and systemic complications. According to the Japan Neurotrauma Data Bank of the Japan Society of Neurotraumatology, the brain temperature was controlled in 43.9% of severe TBI patients (induced normothermia: 32.2%, hypothermia: 11.7%) in Japan. Brain temperature management was performed mainly in young patients, and the outcome on discharge was favorable in patients who received brain temperature management. Particularly, patients who need craniotomy for removal of hematoma were a good indication of therapeutic hypothermia. Improvement of therapeutic outcomes with widespread temperature management in TBI patients is expected.